Epistemologi Empirisme - Fitri, Nurul Amalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Knowledge is a fundamental aspect of human life. One branch of philosophy that discusses knowledge is epistemology. In the development of philosophy, there are various schools of thought that try to explain how knowledge is obtained, and two of the most influential are rationalism and empiricism. This study is a literature review with a qualitative descriptive approach. The main data in this study is literature data used to see the epistemology of empiricism in the philosophy of science. The data collected is coded, then reduced and finally conclusions are drawn based on qualitative analysis. The results of the study show that Epistemology is a branch of philosophy that studies knowledge, its origins, limitations, and truth. In epistemology, there are fundamental questions such as: